Director of the CUTIng Edge center. - Boglou, Dimitrios (My University, 2026)
The centre provides workshops for entrepreneurship, soft skills and digital literacy skills, leadership training. The centre also provides all the photography and videography needs for the Cyprus University of Technology. During the year 2021, it participate and covered in more than 100 events.